Representasi Budaya dalam Menu Sundaland di Restoran Mari Merangkai Bunga Seroja (MMBS) - Yosi Anisa Basmahulwah; Dede Kosasih; Dian Hendrayana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the representation of Sundanese culture in the Sundaland menu served at Mari Merangkai Bunga Seroja (MMBS) restaurant in Bandung. Sundaland is a fine dining tasting menu that integrates Sundanese and Thai cuisines within a contemporary fusion cuisine concept. This research employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, documentation, and literature review, analyzed using Roland Barthes' semiotics. The findings reveal that the Sundaland menu represents Sundanese culture through seven cultural elements: religious system, social system, knowledge system, language, arts, livelihood system, and technology and tools. These representations are conveyed symbolically through ingredient selection, cooking techniques, menu naming, presentation aesthetics, and gastronomic narratives accompanying the dining experience. Conceptually, this study affirms that fusion fine dining practices can function as a space for local cultural identity, while broadening the understanding of gastronomy as cultural communication in a modern context.